Customer relationship management (CRM): SMS technology for auto dispatching in data restoration tracking system / Mohd Najmuddin Mohd Hassan - Mohd Hassan, Mohd Najmuddin (2004)
Customer Relationship Management (CRM) is the connection between customer satisfaction and future success in business. CRM is becoming critical to organizations worldwide as global competition increases and technological innovations in communication continue to emerge. Primacare is a call center in Telekom Malaysia that manages the fault restoration of data services for priority corporate customers. These data services are also known as Private Leased Circuits (PLC). Currently there are about 17,000 PLC lines provisions in the Telekom Malaysia's Network. Primacare handles approximately 25% (4,000) of the total fault restorations monthly. Shorter restoration time is ideal in achieving high customer satisfaction. Long interruptions to these services may cause diminution in revenue to the customer. The purpose of this study is to assess and improve the quality of data fault handling to achieve higher standards of customer satisfaction. The approach is to make use of the current advanced technology in integrating tracking visibility to Primacare centre. The project embarks in Short Messaging System (SMS) technology as a solution in providing an efficient and cost effective application. The main problem or challenges that are foreseen in this study is the technique of interfacing with existing databases and systems and providing tools for the field force and supervisors to interact with the systems.